DRUG UTILIZATION PATTERN OF ANTI-DIABETIC DRUGS IN A RURAL AREA OF TAMILNADU, SOUTH INDIA – A PROSPECTIVE, OBSERVATIONAL STUDY - V. SIVASANKARI,M.D; E.MANIVANNAN,M.D; S.P.PRIYADARSINI,M.D (International Journal of Pharma and Bio Sciences, 2013)
Diabetes mellitus is in alarming rise from 40 million to 70 million people by 2025 in India. Drug utilization studies help to identify the treatment of adherence problems and improve proper drug usage. To evaluate the drug utilization pattern of anti-diabetic drugs in Type II DM patients in a rural population. A prospective observational study was carried out at Seeragapadi village, Salem for a period of 6 months. Out of 1456 patients screened, 92 Type II DM patients were included and a structured questionnaire was used to collect datas and analysis done. The prevalence was about 6.3% and 68.47% of them were in 40 to 60 years of age. Hypertension was the most common co morbid condition (19.6%) followed by hypercholestremia (3.3%). Totally 21.74% of patients were on monotherapy and Metformin was commonly prescribed. In combination therapy, Glibenclamide and Metformin (35.86%) were mostly consumed followed by Glimepiride and Metformin (9.78%) and inj. Human Mixtard with Metformin (27.17%). Statins were co-administered in 5.5% of patients and there was no evidence of Polypharmacy. Type II DM was treated effectively with both Insulin and Oral hypoglycemic drugs. Glimepiride can be substituted for Glibenclamide due to better pharmacokinetic and pharmacodynamic properties. Statins and low dose ACE inhibitors can be added according to recent ADA guidelines to minimize the complications of DM.